A tax plan for endogenous innovation - M. M. Croce; A. G. Karantounias; Stephen Raymond; Lukas Schmid (Federal Reserve Bank of Atlanta, 2017)
In times when elevated government debt raises concerns about dimmer global growth prospects, we ask: How can the government provide incentives for innovation in a fiscally sustainable way? We address this question by examining the Ramsey problem of finding optimal tax and subsidy schemes in a model in which growth is endogenously sustained by risky innovation. We characterize the shadow value of growth and entry in the innovation sector. We find that a profit tax is required to replicate the first-best in order to balance the externalities associated with innovative activity. At the second-best, the profit tax is designed to optimally respond to growth shocks above and beyond what is prescribed by the standard tax-smoothing incentives in economies with exogenous growth. The interplay of risk and innovation opens a new margin for optimal taxation.
Keywords: E32; E62; H21; H63; O3; 330; innovation; R&D investment; endogenous growth; government debt; labor tax; subsidy; profit tax